Spray-dried chitosan/acid/NaCl microparticles enhance saltiness perception. (15th September 2017) - Yi, Cheng; Tsai, Min-Lang; Liu, Tristan
Highlights: Spray-dried chitosan/acid/NaCl microparticles were hollow and pleasantly hygroscopic. Size of chitosan/acid/NaCl ranged from 15.4–32.0 μm, raised with NaCl concentration. NaCl crystals of lactic acid group had size of 1–4 μm and most on particle surface. NaCl crystals of acetic acid group had size of 1–2 μm and most on particle matrix. Acetic/lactic acid groups were saltier than normal salt and could be a low-Na salt. Abstract: The composition, physicochemical properties and salinity of spray-dried chitosan/acid/NaCl microparticles were tested to ensure a low-sodium and high-salinity salty agent. The spray-dried chitosan/acid/NaCl microparticles were hollow and had a favourable hygroscopicity, and increased NaCl content and decreased organic acid content. Their size of the microparticles was 15.4–32.0 μm and increased with NaCl concentration. The microparticles of acetic and lactic acid groups had a NaCl crystal size of 1–2 and 1–4 μm, respectively. The NaCl crystals of acetic, lactic and citric acid group microparticles were distributed on the microparticle matrices, mostly on the microparticle surface and mainly on the inner walls of the microparticles walls, respectively. The acetic and lactic acid group microparticles were relatively smaller than general salt, with NaCl crystals distributed on the particle surfaces. Consequently, they were perceived as saltier than general salt and could potentially be regarded as a low-sodium salt for surface-salted foods.